2022
DOI: 10.1097/cad.0000000000001410
|View full text |Cite
|
Sign up to set email alerts
|

Long-term response of more than 9 years to regorafenib in a heavily pretreated patient with metastatic colorectal cancer

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide, with approximately 1.9 million new diagnoses and 935 000 deaths annually. Overall, there is accumulating evidence that receiving all available treatments leads to a survival advantage and, although tailored treatments might be appropriate for selected patients, the one-size-fits-all approach is still widely used in chemo-refractory patients. Currently, different antiangiogenics and multitarget agents are indicated in treatment of metastatic CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Every effort should be made to identify clinical and molecular biomarkers predictive of response. Potential factors associated with treatment response to antiangiogenics and multitarget agents included LDH, hERG1/aHIF-2α expression, the circulating angiopoietin-2 level, but results should be confirmed in prospective studies [ 27 , 48 , 49 , 50 , 51 ]. An exploratory analysis from the CORRECT trial showed an association between HFS reaction and survival benefit from regorafenib, and a similar differential benefit was observed for fruquintinib in a post-hoc analysis of the FRESCO trial [ 52 , 53 ].…”
Section: Brief Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every effort should be made to identify clinical and molecular biomarkers predictive of response. Potential factors associated with treatment response to antiangiogenics and multitarget agents included LDH, hERG1/aHIF-2α expression, the circulating angiopoietin-2 level, but results should be confirmed in prospective studies [ 27 , 48 , 49 , 50 , 51 ]. An exploratory analysis from the CORRECT trial showed an association between HFS reaction and survival benefit from regorafenib, and a similar differential benefit was observed for fruquintinib in a post-hoc analysis of the FRESCO trial [ 52 , 53 ].…”
Section: Brief Discussionmentioning
confidence: 99%
“…Its efficacy in heavily pretreated patients may be due to the broad spectrum of anti-kinase activity, which conversely, may imply a higher incidence of adverse events (AE). However, a narrower range of targets might minimize off-target toxicities and improve the clinical outcome due to a higher drug exposure at the maximum tolerated dose (MTD) [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%